An Analysis of the Effect of Mandatory Adoption of International Financial Reporting Standards (IFRS) on Earnings Management in U.K Firms - HU, QING (2016)
In this paper, I investigate whether the mandatory IFRS adoption can reduce the earnings management in UK firms. The results of all three different methods suggest that earnings management has reduced after the mandatory adoption of IFRS in UK firms. The conclusion highlights the importance of a relatively high quality accounting standard to earnings quality. I suggest that the IASB should make their efforts to create higher quality accounting standard and require companies to adopt it.